Hyponymy as a Contrast Method in the Internet Game “Antiphrases” - CHEN, Yaxing; BOCHINA, Tatyana Gennadevna; HUA, Li (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study is based on the Internet game, using antiphrases-puzzles that are created by Runet users playing with precedent units and replacing all the words of the prototype with contrasting ones. The relevance of the study is motivated by the interest of modern linguistics in the phenomenon of the precedent unit. The object of the study is antiphrases and their precedent prototypes, in which contrasting word replacements are made according to the aspect-aspect principle. The article concludes that most often contrastive replacements are made for such groups of co-hyponyms as somatisms, coloratives, names of relatives, zoonyms and names of food.RESUMEN El estudio se basa en el juego de Internet, que utiliza acertijos de frases, creados por usuarios de Runet que juegan con unidades precedentes y reemplazan todas las palabras del prototipo por otras contrastantes. La relevancia del estudio está motivada por el interés de la lingüística moderna en el fenómeno de la unidad precedente. El objeto del estudio son las antifrases y sus prototipos precedentes, en los que los reemplazos de palabras contrastantes se realizan de acuerdo con el principio de aspecto-aspecto. El artículo concluye que la mayoría de las veces se hacen reemplazos contrastantes para grupos de co-hipónimos como somatismos, colorantes, nombres de familiares, zoónimos y nombres de alimentos.